Combustion and emission characteristics of solid waste from dioctyl phthalate production. Issue 2 (6th November 2020) - Sun, Zhiguo; Fan, Jiaming; Feng, Run; Wang, Menglu; Zhou, Yue; Zhang, Li
Abstract: BACKGROUND: A novel combustion process of solid waste from dioctyl phthalate (SWDOP) production was developed. The SWDOP is high in organic combustible components, has high calorific value, low ash content and no halogen element and is especially suitable for combustion treatment. The combustion and emission characteristics of SWDOP under various conditions in a tube furnace were investigated. RESULTS: Major pollution factors detected in flue gas include CO, volatile organic compounds (VOCs), particles and NO. The combustion of SWDOP happens in two stages. Most DOP escapes from activated carbon and oxidizes to VOCs between 150 and 270 °C, and the activated carbon burns together with the little residual DOP between 270 and 525 °C. Moreover, thermogravimetry was employed to study the effects of combustion of SWDOP. There are two strong and narrow peaks at around 250 and 420 °C in the differential thermogravimetry curve since DOP evaporates rapidly at 250 °C, and activated carbon burns intensely at 420 °C. The peak concentration of VOCs during combustion is 245.4 mg m −3 at 250 °C and 254.9 mg m −3 at 400 °C. Among all VOCs, toluene concentration is the largest, accounting for 70%. The generated CO concentration decreases with increasing air flow. Varied‐mesh screens were used to intercept and detect the particle matter from flue gas, while particle size distributions and scanning electron microscopy analyses were carried out. The amount of condensates from the flue gas is increased as the air flow increases. It was determined from Fourier transform infrared analysis that both the SWDOP sample and the flue gas contain DOP. CONCLUSIONS: The results obtained in this work suggest that temperature has a great effect on the combustion and emission of SWDOP. Owing to many advantages of this treatment process for SWDOP by combustion, it has great potential for commercial applications. © 2020 Society of Chemical Industry (SCI)